2010
DOI: 10.3109/10715762.2010.532493
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of reactive oxygen species (ROS) with curcumin analogues: Structure–activity relationship

Abstract: Three curcumin analogues viz., bisdemethoxy curcumin, monodemethoxy curcumin, and dimethoxycurcumin that differ at the phenolic substitution were synthesized. These compounds have been subjected for free radical reactions with DPPH radicals, superoxide radicals (O(2)(•-)), singlet oxygen ((1)O(2)) and peroxyl radicals (CCl(3)O(2)(•)) and the bimolecular rate constants were determined. The DPPH radical reactions were followed by stopped-flow spectrometer, (1)O(2) reactions by transient luminescence spectrometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 52 publications
4
34
0
5
Order By: Relevance
“…The methoxy substitution on phenyl ring did not significantly increase the reaction rate constant with superoxide anion radical. 16) Our findings supported the importance of the keto-enol moiety. However, the decrease scavenging activity of Dmc and Bdmc may imply the effect of the ortho-methoxyphenolic group.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The methoxy substitution on phenyl ring did not significantly increase the reaction rate constant with superoxide anion radical. 16) Our findings supported the importance of the keto-enol moiety. However, the decrease scavenging activity of Dmc and Bdmc may imply the effect of the ortho-methoxyphenolic group.…”
Section: Resultssupporting
confidence: 77%
“…This may be related primarily to the differences in the ability to donate hydrogen atoms from a phenolic vs. enolic group due the differences in their chemical structure. [7][8][9]15,16,24,25) The additional hydroxyl group in OHC and the hydrogen atom from the central methylenic group may also contribute to the hydrogen donating ability of these hydrogenated derivatives. 26) In addition, the results confirmed that loss of the orthomethoxyphenolic group in Bdmc caused a greater loss of hydrogen donating activity, whereas the molecule with an ortho-methoxyphenolic group and β-diketone moiety showed the comparable activity to trolox.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress induced by lipid peroxidation may lead to membrane permeability that would allow muscle constituents such as CK and aminotransferases to escape (30). The phenolic compound of curcumin acts as a scavenger of reactive oxygen species and a quencher of the lipid peroxidative side chain (31) prevented CK leakage and other related enzymes from cell membranes and consequently less increase in CK serum level. Previous studies have confirmed that supplements containing antioxidants are able to attenuate these enzymes (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is the most able to suppress TNF-induced NF-κB activation, followed by DMC and BDMC. In contrast, when pro-oxidant activity was examined, BDMC was maximally active at inducing ROS, whereas curcumin and DMC had minimal activity, suggesting that these compounds elicit anti-tumor activity through different mechanisms [41] . Nevertheless, the piperidin-4-one curcumin analog EF-24 has been shown to induce apoptosis by upregulating cellular antioxidant responses [42] .…”
Section: Discussionmentioning
confidence: 92%